Uji Aktivitas Insektisida Ekstrak Daun Serai Terhadap Ulat Daun Kubis (Plutella xylostella L.) di Laboratorium - Shahabuddin Shahabuddin; Alam Anshary (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The study was conducted to evaluate effects of varied concentrations of methanol extract of lemon grass, Andropogon nardus L. (10.5%, 9.5%, 8.5%, 7,5%, 6.5%, and 0% as control) on mortality and feeding activity of the third-instars of P.xylostella larvae. It was used a randomized complete design with three replicates. The results showed that the leaf extract of Andropogon nardus at 8.5 % was the best treatment as it could caused high mortality of P. xylostella (66.67 %) and it was able to deter the feeding activity up to 82.66 %. The data suggested that extracts of Andropogon nardus contains toxic oil and feeding activity repellant.